Smart Drug Delivery Strategies for Cancer Therapy - López Mendoza, Carlos Miguel; Alcántara Quintana, Luz Eugenia (Frontiers in Nanotechnology, 2022)
Chemotherapy is one of the most widely used strategies to fight cancer, although it has disadvantages, such: accumulation and, unspecificity by the tumor, among others, resulting in adverse effects on the patient that limit the dose or follow-up with the same. However, the treatment can also fail due to the resistance mechanisms that cancer cells have to these agents. Because of these limitations, smart drug delivery devices have been developed to overcome treatment challenges. These are made with the aim of passively or actively releasing the drug into the tumor environment, increasing the uptake of the chemotherapeutic agent by the cancer cells, thus reducing the adverse effects on other vital organs. Also, these devices can be guided with molecules on their surface that interact with the tumor microenvironment or with specific receptors on the cancer cell membrane, thus conferring specificity. This mini review summarizes advances in the development of devices for cancer treatment, including different smart nanocarriers with single or dual functions. At the same time, we highlight the toxicity and delivery of these devices’ in vivo models. Despite innovation in smart delivery devices, there are still biodistribution and customization challenges to be overcome in future research.